Report to participating governments on the Asian regional employment information training course. Vigyan Bhavan, New Delhi, India, 14 October-8 November 1957 (I.L.O., 1958)
International Labour Office. Expanded programme of technical assistance. ILO/TAP/AFE/R.5. Stencil.